2021
DOI: 10.1371/journal.pone.0252716
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between femoral block and PENG block in femoral neck fractures: A cohort study

Abstract: Background Regional analgesia is worth performing in the multimodal postoperative management of hip fracture (HF) because it reduces hospital morbidity and mortality. The aim of this study is to compare the efficacy and side effects of the recently described “Pericapsular Nerve Group (PENG) Block” with those of the femoral block, which is considered the standard of care for postoperative pain control after femoral neck fracture. Materials and methods We conducted a comparative observational study at a univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 20 publications
0
41
0
4
Order By: Relevance
“…The ultrasound guided peripheral nerve blocks including fascia iliaca block (FIB), femoral nerve block (FNB), and lumbar plexus block are commonly utilized opioid-sparing techniques for hip surgeries [1][2][3][4]. The anterior hip capsule is innervated through articular branches of the femoral nerve, obturator nerve, and accessory obturator nerve as confirmed through prior anatomic studies, signifying that all these nerves must be the key targets regarding hip pain control that may be blocked through PENG block [5].…”
Section: Introductionmentioning
confidence: 99%
“…The ultrasound guided peripheral nerve blocks including fascia iliaca block (FIB), femoral nerve block (FNB), and lumbar plexus block are commonly utilized opioid-sparing techniques for hip surgeries [1][2][3][4]. The anterior hip capsule is innervated through articular branches of the femoral nerve, obturator nerve, and accessory obturator nerve as confirmed through prior anatomic studies, signifying that all these nerves must be the key targets regarding hip pain control that may be blocked through PENG block [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among clinical studies utilizing PENG block ( n = 29), most are low-quality case reports/series [ 1 , 2 , 3 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], but one cohort study [ 59 ] and eight randomized controlled trials [ 4 , 5 , 60 , 61 , 62 , 63 , 64 , 65 ] appeared in the literature after late 2020. Definite post-procedural quadriceps weakness after PENG block was reported in two case reports [ 2 , 3 ] and two RCTs [ 4 , 5 ] (group A).…”
Section: Resultsmentioning
confidence: 99%
“…Allard et al concluded that Twenty-four hours after surgery, two (9%) patients in the "PENG block" group reported having a VAS ≥ 4, versus three (14%) patients in the "femoral block" group (p = 1.00) was non-significant when compared. [9] Archarya et al also presented a drop in the VAS scores to 2&3 in his case report with treatment of PENG block. [10]…”
Section: Pathological Discussion With Figuresmentioning
confidence: 81%
“…[8] Thus theoretically it covers a larger areas than the femoral block. [9] The out-of-plane technique was used in the current patient aiding to its ease in accessibility and visualisation. Archarya et al stated the difficulties and inconsistencies encountered while using the in-plane approach as the AIIS and femoral vessel proved to be a hindrance during drug delivery.…”
Section: Pathological Discussion With Figuresmentioning
confidence: 99%